Formation of fibrillar crystals strongly accelerates the form II to I transformation of polybutene-1 - Zhang, Jiaqi; Liu, Chang; Zhao, Xintong; Zhang, Zhijie; Chen, Quan (Soft matter, 2020)
This study examines the shear-induced formation of fibrillar form II crystals and subsequent form II to I transformation of an isotactic polybutene-1 sample through a combination of rheology, polarized optical microscopy (POM), and small- and wide-angle X-ray scattering (SAXS and WAXS) measurements. Strong shear flow was applied using a strain-controlled rheometer with parallel plate geometry, for which the shear rate increases linearly from the center to the perimeter. Highly oriented crystals were created by the shear flow, leading to the birefringent region shown in the POM images, which propagated from the perimeter to the center with increasing applied shear rate. The form II to I transformation, traced by WAXS, was greatly accelerated with increasing shear rate. This trend is explained as being due to the formation of fibrillar crystals and accordingly a large amount of highly oriented chains tethered between the crystal lamellae. The stress sustained by these tethered chains facilitates the nucleation of form I thereby accelerating the form II to I transformation. This study finds that the form II to I transformation of isotactic polybutene-1 is greatly accelerated when fibrillar form II crystals have been induced by the shear flow, and a degree of this acceleration increases with the shear rate.